On the mathematical theory of globally optimal planned economic systems - Hua, Loo-Keng (1984)
Applying a theorem of non-negative matrix to an economic system, we obtain the rate of growth of the system and the ratio between the sectors of production. Accordingly, we establish a positive eigenvector method for planning economics.